1999
DOI: 10.1046/j.1365-2249.1999.00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of murine IgE and immediate cutaneous hypersensitivity responses to ovalbumin by the immunomodulatory agent leflunomide

Abstract: SUMMARYLeflunomide has been identified as an immunoregulatory and anti-inflammatory compound. Allergic disease is characterized by elevated serum IgE levels, production of allergen-specific IgE and the release of inflammatory mediators from mast cells and granulocytes. Here we demonstrate, using an in vivo murine model, the ability of leflunomide to down-regulate levels of total and allergen-specific serum IgE production. Mice receiving leflunomide (45 mg/kg) orally at the time of primary immunization with ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
(34 reference statements)
2
16
1
Order By: Relevance
“…Recently, we have demonstrated that IL-10-treated DC are able to inhibit allergen-specific Th1 and Th2 cytokine production by T cells from atopic individuals in vitro [8]. In the present study, we used the well-established mouse models of type I allergy and of allergic inflammation [24] to analyze the effect of transfer of IL-10-treated DC in vivo on the development of Th2 responses induced by intraperitoneal injections of low doses of OVA/alum. We have demonstrated that in contrast to transfer of OVA-pulsed, but IL-10-untreated, DC prior to sensitization, which led to enhanced proliferation and cytokine production by mesenterial lymph node cells after restimulation with OVA in vitro, transfer of OVA-pulsed IL-10-treated DC did not increase CD4+ T-cell proliferation nor Th1 and Th2 cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have demonstrated that IL-10-treated DC are able to inhibit allergen-specific Th1 and Th2 cytokine production by T cells from atopic individuals in vitro [8]. In the present study, we used the well-established mouse models of type I allergy and of allergic inflammation [24] to analyze the effect of transfer of IL-10-treated DC in vivo on the development of Th2 responses induced by intraperitoneal injections of low doses of OVA/alum. We have demonstrated that in contrast to transfer of OVA-pulsed, but IL-10-untreated, DC prior to sensitization, which led to enhanced proliferation and cytokine production by mesenterial lymph node cells after restimulation with OVA in vitro, transfer of OVA-pulsed IL-10-treated DC did not increase CD4+ T-cell proliferation nor Th1 and Th2 cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…ELISA for determination of ␤gal-specific antibodies in serum ␤Gal-specific antibodies of different isotypes (IgG1, IgG2a, IgE) were measured using an antigen capture ELISA as reported 56 with modifications. All reagents except the blocking buffer were used in volumes of 100 l/well.…”
Section: Gene Therapymentioning
confidence: 99%
“…It has been shown previously that protein A, a cell wall component of most S. aureus strains, exhibits immunomodulatory properties, including the induction of Th1 responses after intraperitoneal administration [35]. Therefore, it was tempting to speculate that the expression of protein A might contribute to the Th1-biasing capacity of S. aureus particles.…”
Section: Resultsmentioning
confidence: 99%
“…Allergen sensitization of mice was induced by repeated intraperitoneal injection of 10 µg ovalbumin (OVA Grade VI; Sigma-Aldrich, Deisenhofen, Germany) adsorbed to aluminum hydroxide (alum; Pierce, Rockford, Ill., USA) at intervals of 2 weeks [35]. In order to determine the effect of application of S. aureus on the OVA-specific immune response, mice were injected with a total volume of 200 µl containing OVA/alum and 10 9 formalin-fixed S. aureus particles, Cowan I strain (SACS; Pansorbin; Calbiochem-Merck Biosciences, Bad Soden, Germany) or protein A-free Wood 46 strain (SAWS; Sigma-Aldrich) as indicated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation